2008
DOI: 10.1097/mbc.0b013e3282f38c5f
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden mutation and type 1 diabetes mellitus

Abstract: Diabetes mellitus is considered to cause a tendency for arterial thrombosis. Recent studies addressed the association between venous and arterial disease. Resistance to activated protein C is one of the most common causes of venous thrombosis and linked to a single point mutation in the factor V gene, designated as factor V Leiden mutation. There is little information regarding the status of factor V Leiden mutation in type 1 diabetes. The aim of this study is to evaluate association among activated protein C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…In one study, a relation between factor V Leiden and diabetes was indicated whereas other studies failed to show association between factor V Leiden and prothrombin G20210A with diabetes [11][12][13]34]. In our present study, we did not detect an association between factor V Leiden, prothrombin G20210A variant and MTHFR C677T with diabetes.…”
Section: Discussioncontrasting
confidence: 81%
“…In one study, a relation between factor V Leiden and diabetes was indicated whereas other studies failed to show association between factor V Leiden and prothrombin G20210A with diabetes [11][12][13]34]. In our present study, we did not detect an association between factor V Leiden, prothrombin G20210A variant and MTHFR C677T with diabetes.…”
Section: Discussioncontrasting
confidence: 81%
“…However, it is already not known why such patients with diabetes develop more vascular complications both as atherothrombosis (of any district) as VTE and other patients with diabetes do not develop vascular complication. In previous years several research suspected a relationship between diabetes and FVL gene variants both for type 1 or type 2 diabetes but not univocal data were found [ 14 - 16 ]. Krekora et al in fact suspected also a possible genetic co-segregation for both inherited disorders (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A possibile relationship between the presence of FVL gene variant and type 1 or type 2 diabetes has been hypothysed by several reports in the Literature with non-univocal findings [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%